The Origins Of Language: Unraveling Evolutionary Forces - Masataka, Nobuo (Springer, 2008)
Developments in Cognitive Science indicate that human and nonhuman primates share a range of behavioral and physiological characteristics that speak to the issue of language origins. This book has three major themes, woven throughout the chapters and the book will be of great interest to scientists who are interested in language, including linguists, biologists, psychologists, anthropologists and neuroscientists.